Phenol degradation catalyzed by a peroxidase mimic constructed through the grafting of heme onto metal-organic frameworks. (January 2018) - Jiang, Wei; Yang, Jiebing; Wang, Xinghuo; Han, Haobo; Yang, Yan; Tang, Jun; Li, Quanshun
Graphical abstract: Highlights: Peroxidase mimic was constructed through the conjugation of heme with metal-organic frameworks. The morphology of enzyme mimic was characterized. The enzyme mimic exhibited high phenol removal ability. The enzyme mimic could avoid the iron residues in the phenol removal. The enzyme mimic possessed good recyclability in the phenol removal. Abstract: The aim of this work was to construct a peroxidase mimic for achieving the phenol degradation through Fenton reaction. The enzyme mimic was synthesized through the conjugation of heme with the amino group of 2-amino-1, 4-benzene dicarboxylate in UiO-66-NH2 (ZrMOF), namely Heme-ZrMOF. Compared to free heme, the composite Heme-ZrMOF exhibited an obviously enhanced ability for phenol degradation with up to 97.3% of phenol removal after 2 h. Meanwhile, it could achieve the easy separation of catalyst from the system and the elimination of iron residues in the process of phenol degradation. Finally, the catalyst Heme-ZrMOF was observed to possess good recyclability in the phenol degradation with still 76.2% of phenol removal after 4 cycles.